Indirect Reciprocity under Incomplete Observation - Nakamura, Mitsuhiro; Masuda, Naoki (PLOS Computational Biology, 2011)
Author Summary Humans and other animals often help others even when the helping behavior is costly. Several mechanisms can explain the emergence and maintenance of cooperation. In one such mechanism called indirect reciprocity, individuals are rated according to their past behavior toward others. Individuals help others with a good reputation but not those with a bad reputation. Indirect reciprocity is relevant in relatively large societies where individuals do not meet each other repeatedly. Then, unless an authority maintains the reputation of individuals, individuals would not know information about some others even indirectly via gossip. We investigated a model in which both individuals playing the game (acting players) and observers of the game, who evaluate acting players and start gossiping, incompletely perceive others. In the unique viable and cooperative strategy, one cooperates with good and unknown peers and defects against bad peers. Populations of suspicious observers under which cooperation (defection) to unknown peers is regarded to be good (bad) enable cooperation in relatively wide parameter regions. In contrast, populations of trustful observers under which both cooperation and defection to unknown peers are regarded to be good are relatively efficient.